2020
DOI: 10.1001/jamanetworkopen.2020.15927
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intratumoral and Peritumoral Computed Tomography Radiomics for Predicting Pathological Complete Response to Neoadjuvant Chemoradiation in Patients With Esophageal Squamous Cell Carcinoma

Abstract: Key Points Question Are peritumoral radiomics features extracted from pretreatment computed tomography images predictive of pathological complete response following neoadjuvant chemoradiation in patients with esophageal squamous cell carcinoma? Findings In this diagnostic study of 231 patients, the developed model integrating intratumoral and peritumoral radiomics features achieved improvement of predictive performance (area under the receiver operating cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 56 publications
2
111
0
Order By: Relevance
“…Three articles were conducted by Beukinga et al (14)(15)(16), therefore we only chose one of these for further analysis. Two articles were conducted by Hu et al (17,18), therefore we selected only one of them for the subsequent analysis. As a result, seven articles were chosen for quantitative meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three articles were conducted by Beukinga et al (14)(15)(16), therefore we only chose one of these for further analysis. Two articles were conducted by Hu et al (17,18), therefore we selected only one of them for the subsequent analysis. As a result, seven articles were chosen for quantitative meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The second-order class includes the graylevel (GL) co-occurrence matrix, GL run-length matrix, GL size-zone matrix, GL distance-zone matrix, neighborhood gray tone difference matrix, and neighboring GL dependence matrix (8). We reviewed the radiomics feature type used and other types of features of the selected articles, and the results are provided in Table III (19), four studies used the first-order feature (17,(20)(21)(22), and five studies used the second-order feature (14,17,(21)(22)(23).…”
Section: Review Of Type Of Radiomics Feature and Other Features In Selected Studies According To International Symposium Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published studies ( n = 12) focused on the prediction of treatment response for patients receiving chemoradiotherapy or nCRT [ 83 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. The ML algorithms achieved an AUC of 0.78–1.00.…”
Section: A Review Of Literature Using Machine Learning and Radiomics Applications In Ecmentioning
confidence: 99%
“…Yang et al [ 102 ] developed three predictive models for treatment response after nCRT and noted that overfitting was a problem for small sample size studies. Hu et al [ 101 ] found that a combination of peritumoral radiomics features appeared to improve the predictive performance of intratumoral radiomics for pre-treatment prediction of pCR (AUC = 0.85, 95% CI, 0.75–0.95) for nCRT using CT radiomics features, with a cohort of 231 patients and external validation of the results. The same cohort of patients was used for the exploration of the transfer learning approach and the results showed that ResNet50-based deep learning features had the predictive ability for treatment response in esophageal SCC [ 83 ].…”
Section: A Review Of Literature Using Machine Learning and Radiomics Applications In Ecmentioning
confidence: 99%